PERAN REGULASI EMOSI TERHADAP PERILAKU MENCARI PERTOLONGAN PADA KORBAN KEKERASAN DALAM PACARAN DI DEWASA AWAL - Sy, Vinna Ramadhany; Medellu, Gita Irianda Rizkyani; Kusumawardhani, Sri Juwita (Journal of Research and Measurement in Psychology: JPPP, 2024)
The stage of early adulthood in human development is to establish romantic relationships with the opposite sex. Therefore, having a romantic relationship is important for individuals at that age. Out of these four types of violence, emotional violence is the one that cannot be seen in real life, and even the victims don't really feel that what they are experiencing is a form of emotional violence. In emotional violence, the perpetrator will play a role by manipulating the victim, so that the victim does not even realize what he is experiencing, but gradually the impact of the violence is felt in everyday life. Meanwhile, the position of victims who are manipulated and unaware of the violence they experience, makes them feel that their perception of the situation they are experiencing is unrealistic, victims usually do not recognize or recognize emotional violence, and they develop coping mechanisms such as denial and minimize the violence they experience. With this condition it is difficult for victims to seek help for what they are experiencing. There are predictors that can influence the behavior of seeking help, including the regulation of the victim's emotions, the intensity of the search for help itself, and so on. In order to seek help from a manipulative, emotionally abusive state, the victim must have trust in others. Conditions that are astonishing and difficult to understand and believe are like victims of natural emotional abuse, forcing them to only want to open up to people they truly trust.